Arterial aging and subclinical arterial disease are fundamentally intertwined at macroscopic and molecular levels - Lakatta, Edward G; Wang, Mingyi; Najjar, Samer S (The Medical clinics of North America, 2009)
The structure and function of arteries change throughout a lifetime. Age is the dominant risk factor for hypertension, coronary heart disease, congestive heart failure, and stroke. The cellular/molecular proinflammatory alterations that underlie arterial aging are novel putative candidates to be targeted by interventions aimed at attenuating arterial aging as a major risk factor for cardiovascular diseases. This review provides a landscape of central arterial aging and age-disease interactions, integrating perspectives that range from humans to molecules, with the goal that future therapies for cardiovascular diseases, such as hypertension, also will target the prevention or amelioration of unsuccessful arterial aging.